2018
DOI: 10.3390/w10040495
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Suitable Areas for Home Gardens for Irrigation Potential, Water Availability, and Water-Lifting Technologies

Abstract: Abstract:The study was conducted in Lake Tana Basin of Ethiopia to assess potentially irrigable areas for home gardens, water availability, and feasibility of water-lifting technologies. A GIS-based Multi-Criteria Evaluation (MCE) technique was applied to access the potential of surface and groundwater sources for irrigation. The factors affecting irrigation practice were identified and feasibility of water-lifting technologies was evaluated. Pairwise method and expert's opinion were used to assign weights for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Agriculture is the core driver for the economy of Ethiopia and long-term food security which supports about 85% of the population's livelihoods, and 43% of gross domestic product (GDP) [1][2][3]. However, the current farming practices in the nation are mainly traditional tillage using animals and hand tools; which resulted in the loss of soil fertility and crop productivity [4][5][6][7][8]. On the other hand, water is a valuable resource in food production, nevertheless, the competition for water is high among various sectors due to several reasons including population growth, climate change, and poor management of rainwater.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agriculture is the core driver for the economy of Ethiopia and long-term food security which supports about 85% of the population's livelihoods, and 43% of gross domestic product (GDP) [1][2][3]. However, the current farming practices in the nation are mainly traditional tillage using animals and hand tools; which resulted in the loss of soil fertility and crop productivity [4][5][6][7][8]. On the other hand, water is a valuable resource in food production, nevertheless, the competition for water is high among various sectors due to several reasons including population growth, climate change, and poor management of rainwater.…”
Section: Introductionmentioning
confidence: 99%
“…Ineffective on-farm irrigation management practices lead to poor water distribution, nonuniform crop growth, excessive leaching of soil nutrients all of which decrease water and crop productivity [25][26][27]. Conservation agriculture (CA) is found to be an effective strategy in the region to improve soil quality, water management, and crop yield [5,6,28]. Conservation agriculture (CA) is defined as minimal soil disturbance (no-till, NT) and year-round permanent soil cover (mulch) combined with rotation in time [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current farming practice is traditional with poor soil and water management strategies resulting in soil degradation [12][13][14]. Soil degradation is one of the major causes of low agricultural productivity in the region [12,15]. On the other hand, the ever-increasing population demands a significant increase in food supply [16,17] and improvements in the nutritional wellbeing as malnourishment is also a serious challenge in the region [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies including [24,25] indicated that improved water productivity refers to an increase in water sustainability and food security. Irrigation plays an essential role in addressing the high rainfall variability in the region [15,26] and increasing the cycle of crop production [27,28]. Irrigation development in SSA is limited to technologies with higher water use efficiency as water scarcity is a challenge.…”
Section: Introductionmentioning
confidence: 99%